Revised proposal for additional wall attached to diaphragm wall of BRAC University new campus project - BUCG-ABC Joint Venture (Brac University, 2023)
This record consists of general correspondence regarding revised proposal for additional wall attached to diaphragm wall of BRAC University new campus project.